PERANCANGAN SISTEM INFORMASI REKAM MEDIS ELEKTRONIK DALAM PELAPORAN 10 BESAR PENYAKIT RAWAT JALAN DI RSIA YASMIN PALANGKARAYA - Raya Maharani Putri (Indonesian Journal Publisher, 2025)
This study aims to design an electronic medical record information system to support the reporting of the top ten outpatient diseases at RSIA Yasmin Palangkaraya. The previous reporting process was still manual using Microsoft Excel, resulting in delays and inefficiencies. This research used a qualitative method with a waterfall system development approach. Data were collected through observation, interviews, and literature study. The result is an electronic-based information system design that includes flowmap, context diagram, level 0 DFD, and ERD, which aims to improve the effectiveness, efficiency, and accuracy of medical data reporting. This system is expected to help hospitals comply with digital reporting obligations in accordance with existing regulations.